Case Report of Disseminated Pseudomonas Infection with Superadded Burkholderia Infection - A Battle Lost! - Kamath, Dr Sangita; Bharadwaj , Dr Murari; Kumar, Dr Manish; Sunder, Dr Ashok (International Journal of Innovative Research in Medical Science, 2021)
Pseudomonas aeruginosa is a gram-negative pathogen, that often causes nosocomial pneumonia in hospitalized patients. Most of these patients have risk factors for pseudomonas infection. Although uncommon, there have been case reports of previously healthy individuals who developed community-acquired pneumonia (CAP) caused by P. aeruginosa. Such cases have often rapidly progressive course and prove fatal. We, hereby, report a case of pseudomonas pneumonia in a 29-year old immunocompetent patient, who developed disseminated infection and superinfection with yet another nosocomial pathogen, Burkholderia cepacia, eventually leading to septic shock and death, despite appropriate antibiotic therapy.